Regional Workshop for designers monitors responsible for training programs for staff in public and school libraries - Van Patten, Elia María (1981)
In the seminar workshop on formation and training of the personnel in the organization and managing of school libraries librarians were outlined deficiencies in the services. I construct a workgroup integrated by specialists him, where I design a regional workshop for designers monitors responsible for the programs of training for personnel in services of public and school libraries in Latin America.